2013
DOI: 10.1093/jnci/djt210
|View full text |Cite
|
Sign up to set email alerts
|

Role of Focal Adhesion Kinase in Regulating YB–1–Mediated Paclitaxel Resistance in Ovarian Cancer

Abstract: We have identified a novel pathway whereby FAK inhibition with VS-6063 overcomes YB-1-mediated paclitaxel resistance by an AKT-dependent pathway. These findings have implications for clinical trials aimed at targeting FAK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 40 publications
4
141
1
Order By: Relevance
“…More importantly, it was reported that a potential clinical niche for FAK tyrosine kinase inhibitor (TKi) may be used in patients with PCa to overcome chemoresistance because cotreatment with FAK TKi and docetaxel resulted in an additive attenuation of FAK and Akt phosphorylation and overcame the chemoresistant phenotype in PCa PC3 and DU-145 cells (35). Interestingly, FAK inhibition with vs-6063 overcame YB-1-mediated PTX resistance by an AKT-dependent pathway (36) in ovarian cancer. Additionally, the acquisition of drug resistance in ovarian cancer cells induced an extensive reorganization of the actin cytoskeleton, which governed the cellular mechanical properties, motility, and possibly intracellular drug transportation (37).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it was reported that a potential clinical niche for FAK tyrosine kinase inhibitor (TKi) may be used in patients with PCa to overcome chemoresistance because cotreatment with FAK TKi and docetaxel resulted in an additive attenuation of FAK and Akt phosphorylation and overcame the chemoresistant phenotype in PCa PC3 and DU-145 cells (35). Interestingly, FAK inhibition with vs-6063 overcame YB-1-mediated PTX resistance by an AKT-dependent pathway (36) in ovarian cancer. Additionally, the acquisition of drug resistance in ovarian cancer cells induced an extensive reorganization of the actin cytoskeleton, which governed the cellular mechanical properties, motility, and possibly intracellular drug transportation (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pathways in cancer and pathways related to specified cancers (such as prostate and colorectal cancer), 4 pathways including ErbB signaling, focal adhesion, apoptosis and p53 signaling were enriched, suggesting that HNF1B may contribute to drug resistance in ovarian cancer via those pathways. ErbB signaling (91), focal adhesion (92,93), apoptosis (94,95) and p53 signaling (96,97) have been reported to associate with drug resistance in ovarian cancer. For example, miR-21 regulates drug resistance via apoptosis and cellular survival pathways (94), and loss of DOK2 induces carboplatin resistance in ovarian cancer via suppression of apoptosis (98).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also identified cofactors contributing to FAK overexpression (33)(34)(35)(36). FAK overexpression has been associated with breast cancer lung metastasis (37,38), and FAK inhibitors have been introduced in novel therapeutic strategies (20,(39)(40)(41). An association between FAK overexpression and lymphatic metastasis has been identified in non-small-cell lung, oral squamous cell, esophageal, gastric, tongue, laryngeal and endometrial cancer by retrospective analysis of clinical samples (42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 was determined as described previously (20). Briefly, 3,000 cells were seeded in each well of a 96-well plate and allowed to adhere overnight.…”
Section: Spect-ct Imaging In Vivomentioning
confidence: 99%